Learning during covid-19 at elementary schools in Indonesia - Endang Rochyadi; Tryastuti Irawati Belliny Manullang; Sunardi Sunardi (Universitas Negeri Padang, 2021)
The COVID-19 pandemic occurred in Indonesia in early March 2020 which was then followed by learning from home policy. The purpose of this study is to gather information through a survey about the implementation of online learning conducted by teachers who provide inclusive education service at the elementary schools. This study uses a descriptive qualitative approach. The data collected by using a survey technique and then a descriptive analysis is conducted with a total of 80 respondents who are scattered in several provinces in Indonesia. The results show that teachers' knowledge of COVID-19 needs improvement and a few teachers still believe that COVID-19 is a conspiracy. The learning process during the COVID-19 pandemic has made teachers make changes in the teaching and learning process, but not all teachers use television programs as a medium of learning. The ability of teachers to use ICT helps them in providing educational services and the majority have no difficulty using learning applications. Although at the beginning of the pandemic, it was difficult to adapt to learning, until this article is written the teachers have been adapting their teaching approaches. It is also found that teachers have a good relationship with parents and teachers fully aware that the success of distance learning lay in the involvement of parents.